Identifikasi Kandungan Hidrokuinon pada Krim Pemutih yang Beredar di Pasar Tradisional Wilayah Kabupaten Banjarnegara - Sabtanti Harimurti; Ika Sevi Deriyanti; Hari Widada; Pinasti Utami (Universitas Muhammadiyah Surakarta, 2021)
Cosmetics that are sold in the market are in great demand by many women. The type of cosmetics that is often used is a whitening cream. This cream can provide a whitening effect on facial skin so that it can increase self-confidence. One of the ingredients that have skin whitening properties and is often added to whitening creams is hydroquinone. This material has the effect of inhibiting the formation of melanin so that it can whiten the skin. The use of hydroquinone without medical supervision is not allowed because it can have negative effects such as allergies, skin redness, and a burning feeling. In this paper, we will report the identification results of the hydroquinone content in the whitening cream which is not a distribution license number from the BPOM (Indonesia Food and Drug Supervisory Agency) which is marketed in the Banjarnegara Region area. Samples were taken from the Banjarnegara area and the analysis was carried out at the Pharmacy Laboratory of the Universitas Muhammadiyah Yogyakarta. The analytical method used was the identification of the hydroquinone content carried out by the TLC-densitometry method. Qualitative analysis used TLC, where the stationary phase used was silica GF254 while the mobile phase used was toluene - glacial acetic acid at a ratio of 8: 2. Samples were dotted using a microsyringe of 25 µL after extraction. Furthermore, the spot identification was carried out under 254 nm UV light and then the Rf value was calculated. Quantitative analysis was used. It was carried out by densitometry by looking at the area produced by the spots on TLC. In this analysis, the level calculation was carried out by comparing the area of the hydroquinone sample with the area of the positive control hydroquinone multiplied by the known hydroquinone level in the positive control. The results of the qualitative analysis showed that of the 21 samples, there were 6 samples or 28.57% of the samples containing hydroquinone. Quantitative analysis shows the levels in the six samples containing hydroquinone, namely sample no.11: 7,12%, sample no.12: 3.69%, sample no.15: 0.06%, sample no.16: 11.18%, sample no.18: 4.67%, and sample no.19: 1.07%. Based on the results of the analysis, several preparations contain hydroquinone exceeding a safe level of 5%, so it is necessary to regularly check testing and supervision from the authorized institution so that the circulating whitening cream is safe for use by the public.